Treatment Seeking Behavior of University Students During COVID-19 Pandemic - Muhammad Taufik; Anis Adzkiya Rahmah; Tasya Amalia; Hoirun Nisa (KESMAS UWIGAMA: Jurnal Kesehatan Masyarakat, 2022)
Background: The COVID-19 pandemic in Indonesia has a negative impact on treatment seeking behavior, including the public's fear or anxiety to visit health services. Treatment seeking behavior is an individual action to get treatment in overcoming health problems. Treatment seeking behavior to health services can be influenced by various things, such as perceived seriousness, perceived benefits and perceived barriers. Objectives: Determine the relationship between perceived seriousness and perceived benefits with treatment seeking behavior to health services for Public Health students at UIN Jakarta during the pandemic. Research Methods: The study was conducted using cross-sectional approach, sample is calculated using a hypothesis test 2 proportion with the degree of significance of 5% and power of the test by 90% so that the obtained results of the total 124 students with a sampling technique using probability sampling in the form of simple random sampling. Results: This study shows that there is a relationship between perceived seriousness (p=0.003; OR=3,153; 95% CI=1,476 - 6,659) and perceived benefits (p=0.002; OR=3,217; 95% CI=1,502 - 6,892) with behavior seeking treatment for health services among Public Health students at UIN Jakarta. Conclusion: Treatment seeking behavior in individuals can be influenced by themselves or from outside the individual. Factors related to the behavior of seeking treatment are the level of seriousness and the level of individual benefits for the disease he is suffering.